Executive Function Deficits in Seriously Ill Children-Emerging Challenges and Possibilities for Clinical Care - Bluschke, Annet; von der Hagen, Maja; Novotna, Barbara; Roessner, Veit; Beste, Christian (Frontiers in pediatrics, 2018)
The past years have seen an incredible increase in the quality and success rates of treatments in pediatric medicine. One of the resulting major challenges refers to the management of primary or secondary residual executive function deficits in affected children. These deficits lead to problems in the ability to acquire, understand, and apply abstract and complex knowledge and to plan, direct, and control actions. Executive functions deficits are important to consider because they are highly predictive of functioning in social and academic aspects of daily life. We argue that current clinical practice does not sufficiently account for the complex cognitive processes in this population. This is because widely applied pharmacological interventions only rarely account for the complexity of the underlying neuronal mechanisms and do not fit well into possibly powerful "individualized medicine" approaches. Novel treatment approaches targeting deficits in executive functions in seriously ill children could focus on neuronal oscillations, as these have some specific relations to different aspects of executive function. Importantly, such treatment approaches can be individually tailored to the individuals' deficits and can be transferred into home-treatment or e-health solutions. These approaches are easy-to-use, can be easily integrated into daily life, and are becoming increasingly cost-effective.
Keywords: cognitive training; chronic disease; executive function; cognitive dysfunctions; therapy